1997
DOI: 10.1046/j.1365-2141.1997.d01-3153.x
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence

Abstract: We read with interest the report of Harada et al (1995) about a specific chromosome abnormality in CD7-positive acute myeloid leukaemia (AML):t(4;12)(q11;p13).The three cases (two AML-M0 and one AML-M2) evidenced a three-lineage dysplasia, absent or low myeloperoxidase activity, a normal or slightly decreased platelet count and a peripheral blood and bone marrow basophilia in two cases. The immunophenotype was CD7 þ , CD13 þ , CD34 þ , HLD-DR þ and the authors suggested that t(4;12)(q11;p13) is restricted to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The translocation presented as either a single chromosomal abnormality or combined with other abnormalities ( Table 1 ) [ 1 3 4 5 6 7 8 10 11 12 13 14 15 ]. The karyotype of the first patient was 46,XY, t(4;12)(q12;p13),del(5)(q22q35), and del(5q) is a common chromosomal abnormality in myelodysplastic syndrome and in AML with myelodysplasia-related changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The translocation presented as either a single chromosomal abnormality or combined with other abnormalities ( Table 1 ) [ 1 3 4 5 6 7 8 10 11 12 13 14 15 ]. The karyotype of the first patient was 46,XY, t(4;12)(q12;p13),del(5)(q22q35), and del(5q) is a common chromosomal abnormality in myelodysplastic syndrome and in AML with myelodysplasia-related changes.…”
Section: Discussionmentioning
confidence: 99%
“…TO THE EDITOR: Acute myeloid leukemia (AML) with t(4;12) is rare, but its unique morphologic and clinical characteristics have been described in several reports [ 1 2 3 4 5 6 7 8 ]. Most cases show CD7 expression, low or absent myeloperoxidase activity, basophilia, unique blast morphology, dysplastic features, and poor prognosis [ 1 2 3 4 5 6 7 8 ]. Harada et al reported that the incidence among adults is 0.6% [ 1 2 ].…”
mentioning
confidence: 99%